Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4172/2327-5073.1000267
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Outer Membrane Protein OmpC and OmpF on Antibiotics Resistance of E. coli Isolated from UTI and Diarrhoeic Patients in Zaria, Nigeria

Abstract: Multidrug resistant (MDR) E. coli associated infections remains one of the most bacterial infections that have contributed significantly to increased morbidity and mortality in clinical settings. One of the known resistant mechanisms of MDR bacteria is reduced cell wall permeability, which is controlled by outer membrane protein OmpF and OmpC. This study evaluates the difference in molecular weight of outer membrane protein of MDR E. coli isolated from UTI and diarrhoeic patients in Zaria, Nigeria and antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…OmpC and OmpF are two major outer membrane proteins in E. coli which serve as a barrier for antibiotics and other toxic agents entering inside the cell [1]. It is reported that sub lethal dose of antibiotics has protective role in bacterial cell against wide range of antimicrobials [2] and down regulation of porin genes are responsible in nonspecific resistance.…”
Section: Introductionmentioning
confidence: 99%
“…OmpC and OmpF are two major outer membrane proteins in E. coli which serve as a barrier for antibiotics and other toxic agents entering inside the cell [1]. It is reported that sub lethal dose of antibiotics has protective role in bacterial cell against wide range of antimicrobials [2] and down regulation of porin genes are responsible in nonspecific resistance.…”
Section: Introductionmentioning
confidence: 99%